2000
DOI: 10.1148/radiology.214.1.r00ja03253
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Non-Hodgkin Lymphoma: Early Prediction of Outcome with67Ga Scintigraphy

Abstract: Gallium 67 scintigraphic findings after one cycle of chemotherapy and at midtreatment are predictive of outcome in patients with aggressive non-Hodgkin lymphoma. CT findings are not predictive. Early 67Ga scintigraphy during chemotherapy is a good indicator of patients who may benefit from a change to a more aggressive treatment. A future study is necessary to investigate the potential effect of early change of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…19 The results concerning the usefulness of GS in determining the prognosis of patients with lymphoma were equivocal in recent studies. [20][21][22][23] The higher accuracy of FDG in HD, however, was confirmed by direct comparison of the two imaging modalities, 24 and in both HD and NHL a PETbased staging algorithm was found to be more cost-effective than conventional staging mainly based on GS, CT and MRI. 25 The question of prognosis is crucial for further treatment planning and follow-up strategies.…”
Section: Leukemiamentioning
confidence: 96%
“…19 The results concerning the usefulness of GS in determining the prognosis of patients with lymphoma were equivocal in recent studies. [20][21][22][23] The higher accuracy of FDG in HD, however, was confirmed by direct comparison of the two imaging modalities, 24 and in both HD and NHL a PETbased staging algorithm was found to be more cost-effective than conventional staging mainly based on GS, CT and MRI. 25 The question of prognosis is crucial for further treatment planning and follow-up strategies.…”
Section: Leukemiamentioning
confidence: 96%
“…Whereas some authors [16,27] found no differences between these two groups of patients, others [23,28] have reported that patients transplanted with measurable disease at ASCT have a worse outcome. In this sense, 67 Ga scan has successfully been used for many years for this purpose in patients with lymphoma after standard chemotherapy [29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported the usefulness of 67 Ga scintigraphy early after chemotherapy to predict prognosis in patients with nonHodgkin's lymphoma [14,15]. In this respect, 67 Ga SPET might be useful for predicting not only the future fate of the residual viable cell fraction but also patient prognosis.…”
Section: Future Implicationsmentioning
confidence: 99%